Flameless Catalytic LPG Combustion and its Optimization Approach. (2016) - Maharana, Debasis; Soloman, P.A.
Abstract: Catalytic combustion is a highly efficient and modern combustion technique. It incorporates noble metal catalysts to convert the fuel into the products of combustion and provide flameless heat. Flameless heat is appropriate to use in industrial hazardous areas. In this paper catalytic combustion of LPG is carried out with an intension of optimizing the combustion process considering residence time and quantity of excess air as parameters. The optimization was carried out for minimizing amount of unburned fuel. The exhaust gas was analysed using gas chromatograph. The experimentation was designed and optimized using Response Surface Methodology.